RACE AND RELIGION IN EVERYDAY INFORMAITON SEEKING ON SOCIAL MEDIA IN MALAYSIA - Hanchard, Sandra (AoIR Selected Papers of Internet Research, 2014)
This paper investigates the range of social networks that Malaysian users value on social media for information seeking in everyday contexts. It specifically examines whether Malaysian users demonstrate preferences towards connections of shared race or religion on social media. Results from an online questionnaire of 400 Malaysian users, including Bahasa Malay, Chinese, Indian and English speakers demonstrates that social media in general helps users increase their connectedness, both online and offline, with different types of social networks. Malaysian users do not preference ties of shared race or religion over other types of social networks in how they value information for usefulness and trust on social media in everyday contexts. This is an encouraging sign for the potential of social media to promote social cohesion in Malaysia.